Power management of cluster-based DC microgrid system for remote areas - Agustinus Yudhistira Wicaksono Setyanto; Arwindra Rizqiawan; Tri Ardiani (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2025)
Electricity problems in remote areas have become a persistent issue due to various factors, especially economic challenges and lack of accessibility. These issues include frequent blackouts and unstable electricity supply. To address this, a DC microgrid system is one of the electricity solutions because it primarily utilizes renewable energy sources which are often abundant in these areas and offers simpler control than its AC counterparts. Cluster topology for DC microgrid is employed because of its ability to operate both independently and interconnected with several similar systems that suit the electricity needs. To ensure that the system fulfills the electricity needs, a power management strategy is proposed in this paper. The strategy is based on the voltage and battery SoC as the system's local parameters in a decentralized manner. By using decentralized control, the proposed strategy allows the system to operate in both independent and connected configurations. A power transfer scheme between building blocks is also developed as part of the strategy to maximize the power utilization of the system. Simulation and experiment using the DC microgrid model and prototype is conducted to assess the system performance. The results demonstrate the feasibility and effectiveness of the proposed power management strategy, indicating that it could serve as the basis of cluster-based DC microgrid's power management strategy for remote areas.